Analysis of the domestic market of compressor and ultrasonic nebulizers - T. S. Brytanova; A. V. Samko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
The aim of the work is to organize informational files about compressors and ultrasonic nebulizers determination of actuality and availability in marketing analysis of the domestic market.